Cultivation of Religious Moderation Values through Ngidang Tradition in Kelurahan 1 Ulu Palembang - Achmad Fadil; Ani Marlia; Muhammad Ghazali; Dwi Setiawati; Agustri Regita Cahyani; Syarnubi, Syarnubi; Muhamad Fauzi; Septia Fahiroh (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2025)
This research discusses the